Upaya Meningkatkan Jiwa Sosial Anak SEKAMI melalui Katekese Audio Visual - Kristiana Mendrofa (Journal New Light, 2025)
Basically, children need education, guidance, and development through a directed learning process. In the millennial era that continues to grow rapidly, various activities can now be done easily, quickly, and instantly. Today's generation is greatly influenced by the rapid development of technology in the millennial era. Technological improvements have provided valuable opportunities for children to enrich their learning experiences, especially through the utilization of audio-visual catechesis approaches that can enrich their social-emotional aspects. The main goal of this approach is to understand and apply the idea of improving the social aspect of the child through audio-visual catechesis. It is important that children are given the opportunity to fully grow and develop, so that they can smoothly interact in a variety of social situations, ultimately helping them to become overall healthy individuals in church and community life. In order to understand the social psyche more deeply, it is recommended to Catholic Pastoral Officers, Catechists, and Teachers to provide audio-visual catechesis as an effective socialization tool. This activity is an important part of pastoral workers' efforts to support the growth of children today, with the aim of providing them with essential skills and positively engaging social interactions in their lives.